FRI0328 Targeted therapy using intradermal injection of etanercept for remission induction in discoid lupus erythematosus (TARGET-DLE): first results from a proof-of-concept phase 2 trial. (12th June 2018) - Md Yusof, M.Y.; Wittmann, M.; Fernandez, C.; Wilson, D.; Edward, S.; Abignano, G.; Alase, A.; Sharples, L.; Laws, P.; Goodfield, M.J.; Vital, E.M.; Emery, P.
Abstract : Background: A significant proportion of patients with discoid lupus erythematosus (DLE) are resistant to conventional therapies. Tumour necrosis factor (TNF) is pathogenic in DLE. A concern with systemic TNF-i administration is induction of pathogenic autoantibodies and flare of disease. This could be overcome using a low-dose intra-dermal injection, which may be sufficient to neutralise the TNF in lesions, without systemic TNF effects. Objectives: To assess the efficacy and safety of a novel route of administration of a TNF-i using a low dose intra-dermal injection of etanercept (ETN) for remission induction in DLE. Methods: A prospective single arm, Simon's 2-stage minimax design with Hybrid adaptation, phase II open label trial was conducted in Leeds [NCT02656082 ]. Key inclusion criteria were i) adults aged 18–80 y; ii)≥one active DLE lesion and iii) refractory to anti-malarials. One index lesion with the highest activity was treated with weekly intra-dermal injection of up to 10 mg ETN. The primary endpoint was ≥6 patients achieving the modified limited Score of Activity and Damage in DLE (ML-SADDLE) 20 response (defined as reduction ≥20% in total activity comprises erythema, induration and scaling from baseline) at Week 12 for a Phase 3 trial to be recommended. Secondary endpoints included change in objective outcome measures; lesional thermography and laser Doppler imaging. Results: All 25 DLE patients were recruited over 18 months (18 female, mean age 47±12 y, 6 had SLE, 9 had positive ANA and median (range) no. of previous systemic therapies was 5(1–16) 17 patients completed the primary efficacy assessment [Did not attend Week 12 visit=1, early withdrawals=7 (personal choice=2, AE=2, worsening of DLE=1, non-compliance=1, pregnant=1)]. The primary endpoint was met with 13/25 (52%, 95% CI 31–73) meeting the ML-SADDLE 20 in full-set analysis. The rates for ML-SADDLE 50 and 70 were 48% and 20% respectively. Key secondary endpoints were met (table 1). Fifty-one AEs (treatment-emergent=28, Grade 3/4=4) were recorded. There was no worsening of BILAG or SLEDAI in patients with SLE. Trough serum ETN levels were detected in 6/23 (26%). Conclusions: Intradermal injection of ETN substantially reduced clinical activity, met its primary, secondary endpoints and was tolerable in DLE patients who were refractory to anti-malarials and other systemic therapies. This drug warrants further development in multi-centre trials. Analyses of other imaging and histological biomarkers are ongoing and can help stratifying patients for response. Acknowledgements: This research was funded by NIHR (DRF-2014–07–155) and Pfizer IIR Grant (WI188416). The views expressed are those of the author(s) and not necessarily those of the NHS, NIHR or DOH. Disclosure of Interest: M. Y. Md Yusof: None declared, M. Wittmann: None declared, C. Fernandez: None declared, D. Wilson: None declared, S. Edward: None declared, G. Abignano: None declared, A. Alase: None declared, L. Sharples: None declared, P. Laws: None declared, M. J. Goodfield: None declared, E. M. Vital: None declared, P. Emery Grant/research support from: Abbott, BMS, Pfizer, MSD and Roche, Consultant for: BMS, Abbott, Pfizer, MSD, Novartis, Roche and UCB